Is High-intensity Interval Training a Feasible Therapy Option in Geriatric Rehabilitation? A Randomized Controlled Pilot Study - Krüsi, Michael; Bansi, Jens; Sylvester, Ramona; Bachmann, Stefan (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
Background With an increasing number of inpatients in geriatric rehabilitation, there is continuing interest in efficient training measures regarding physical performance.Objectives To examine the feasibility and outcomes of high-intensity interval training (HIIT) in geriatric patients.Methods Single-centre randomized controlled study of HIIT vs. moderate continuous training (MCT) for patients ≥65 years old referred to inpatient rehabilitation. Cardiopulmonary exercise testing (CPET) was performed before the first and last training in order to measure participant’s cardiorespiratory fitness. At the same time-points patients completed a series of questionnaires regarding subjective improvements and acceptance of the training methods.Results Regarding feasibility, HIIT showed a completion rate of 82.4% and an adherence rate of completed sessions of 83.3%. HIIT significantly improved cardiorespiratory fitness (+13% for VO2peak, p=0.01), respiratory quotient (+9%, p=0.01) and power output (+12% for Watt peak, p=0.01) compared with MCT. Significant improvements were also seen over time for physical and mental scores of PROMIS-10 and quality of life.Conclusion A HIIT intervention has proven feasible for elderly patients in a geriatric rehabilitative setting. Further research should specify the HIIT intervention in order to offer this training to more patients. Long-term observations are also needed.
Keywords: Rehabilitation; geriatrics; high-intensity training; interval training; physiotherapy